Performance test of small fishing vessel refrigeration machine for fish storage - Siahaan, Juniawan Preston; Yaqin, Rizqi Ilmal; Demeianto, Bobby; Tumpu, Mula; Abrori, Muhammad Zaki Latif; Priharanto, Yuniar Endri; Pradana, Syahrul (Jurnal Polimesin, 2023)
The refrigeration system in the fishing process is important for maintaining the quality of the catch. However, the design of small-scale refrigeration machines is still not common, so it is an interesting study. Therefore, this study aimed to evaluate the design of small-scale fishing vessel refrigeration machines. Field studies are needed in machine manufacturing to observe the components required to match the refrigeration machine components onboard fishing vessels. This uses a direct observation method to determine the components of the refrigeration machine on the ship. Furthermore, the performance of the machines produced will be tested through the load cooling process. Parameters determined in the performance test include monitoring temperature (suction and discharge), pressure (suction and discharge), evaporator temperature, load temperature, COP (Coefficient of Performance), and compressor power. Refrigerant temperature measurement uses an insulative principle so that ambient temperature does not affect it. The result is that the machine produced has a capacity of 35 l or 15 kg of load. Meanwhile, in the performance test, the COP and electrical power generated while cooling the load for approximately 4 hours were 2,42 and 507 W, respectively. The results of this design were successful and did not experience failure. The significanceof this study can be used as a reference source for making cooling machines for storing the catch of small-scale fishermen.